The Impact of Infection in Pregnancy on Placental Vascular Development and Adverse Birth Outcomes - Weckman, Andrea M.; Ngai, Michelle; Wright, Julie; McDonald, Chloe R.; Kain, Kevin C. (Frontiers in Microbiology, 2019)
Healthy fetal development is dependent on nutrient and oxygen transfer via the placenta. Optimal growth and function of placental vasculature is therefore essential to support in utero development. Vasculogenesis, the de novo formation of blood vessels, and angiogenesis, the branching and remodelling of existing vasculature, mediate the development and maturation of placental villi, which form the materno-fetal interface. Several lines of evidence indicate that systemic maternal infection and consequent inflammation can disrupt placental vasculogenesis and angiogenesis. The resulting alterations in placental hemodynamics impact fetal growth and contribute to poor birth outcomes including preterm delivery, small-for-gestational age, stillbirth, and low birth weight. Furthermore, pathways involved in maternal immune activation and placental vascularization parallel those involved in normal fetal development, notably neurovascular development. Therefore, immune-mediated disruption of angiogenic pathways at the materno-fetal interface may also have long-term neurological consequences for offspring. Here we review current literature evaluating the influence of maternal infection and immune activation at the materno-fetal interface and the subsequent impact on placental vascular function and birth outcome. Immunomodulatory pathways, including chemokines and cytokines released in response to maternal infection, interact closely with the principal pathways regulating placental vascular development, including the angiopoietin-Tie-2, VEGF, and PlGF pathways. A detailed mechanistic understanding of how maternal infections impact placental and fetal development is critical to the design of effective interventions to promote placental growth and function and thereby reduce adverse birth outcomes.